2010
DOI: 10.1186/1749-8546-5-29
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of raw and processed Radix Polygoni Multiflori (Heshouwu) by high performance liquid chromatography and mass spectrometry

Abstract: BackgroundRadix Polygoni Multiflori is the dried root tuber of Polygonum multiflorum Thunb. (Fam. Polygonaceae). According to Chinese medicine theory, raw (R-RPM) and processed (P-RPM) Radix Polygoni Multiflori possess different properties. The present study investigates the differences in chemistry between raw and processed Radix Polygoni Multiflori.MethodsFive pairs of R-RPM and P-RPM as well as 15 commercial decoction pieces were analyzed with high performance liquid chromatography (HPLC) and mass spectrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 13 publications
2
41
0
1
Order By: Relevance
“…ComplicationLiang B.L. 48 2010202030-OctE:59 ± 6 years old ≥ 50Sodium Cantharidinate and vitamin B6 + TACE (MMC, 5-FU, EPI)TACE (MMC, 5-FU, EPI)4weeksComparison of liver function and blood routine examinationC:55 ± 8 years oldLiang C.X. 49 2015303034/26E:median age 53 yearsA and B>80Sodium Cantharidinate and Vitamin B6 + TACE (5-FU, DDP, OXA, EPI)TACE (5-FU, DDP, OXA, EPI)3–4 rounds (15 days per round)1.…”
Section: Resultsmentioning
confidence: 99%
“…ComplicationLiang B.L. 48 2010202030-OctE:59 ± 6 years old ≥ 50Sodium Cantharidinate and vitamin B6 + TACE (MMC, 5-FU, EPI)TACE (MMC, 5-FU, EPI)4weeksComparison of liver function and blood routine examinationC:55 ± 8 years oldLiang C.X. 49 2015303034/26E:median age 53 yearsA and B>80Sodium Cantharidinate and Vitamin B6 + TACE (5-FU, DDP, OXA, EPI)TACE (5-FU, DDP, OXA, EPI)3–4 rounds (15 days per round)1.…”
Section: Resultsmentioning
confidence: 99%
“…One tenth of each group were reserved as materials of RPMR; the rest was subsequently processed. To fix the specific factors involved in the processing, reports in the literature (Li, 2008; Liang et al, 2010; Liu et al, 2011; Chen et al, 2016; Wang et al, 2016) and the Chinese pharmacopeia (2015 edition) (Chinese Pharmacopoeia Commission, 2015) were referenced. Finally, 4 h steaming with black bean (put one layer of water-soaked black beans and one layer of RPMR slices in a pot, repeat the layers, and then steam over boiling water) and then 24 h sun-drying, repeated for a total of 9 cycles, were used as processing conditions.…”
Section: Methodsmentioning
confidence: 99%
“…By quantifying these secondary metabolites using liquid chromatography coupled with diode-array detectors or mass spectrometry (LC-DAD/MS), some previous studies investigated the processing chemistry of PMR. The results showed that processing indeed changed the contents of certain chemicals in PMR (Liang et al, 2010; Liu et al, 2011; Chen et al, 2016; Wang et al, 2016). For example, we previously found that the contents of two anthraquinones (emodin and physicon) in PMR were increased by the processing, while one stilbene glucoside named 2,3,5,4′-tetrahydroxystilbene-2- O -β-D-glucoside (THSG) was decreased (Liang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All tested solutions were filtered through 0.45  μ m membrane syringe filters before use. The method followed [30], and the calibration curve was established for the standards: the concentration range of THSG from 46 to 920  μ g/mL ( Y = 29722 × X − 125033, r 2 = 0.9998), the concentration range of EG from 1.04 to 41.6  μ g/mL ( Y = 52836 × X + 12471, r 2 = 0.9992), the concentration range of emodin from 0.273 to 7.8  μ g/mL ( Y = 66516 × X + 9285, r 2 = 0.9996), and the concentration range of emodin methyl ether from 0.111 to 28.86  μ g/mL ( Y = 67576 × X − 313, r 2 = 0.9998), and the measurement accuracy and precision are favorable, RSD < 5%.…”
Section: Methodsmentioning
confidence: 99%